Electric vehicle industry and sustainable economic growth: A measurement, coupling and causal analysis - Zhao, Xiaolei; Li, Xuemei; Mao, Yumeng; Sun, Jingxiao (Sustainable futures, 2024)
•A stable and upward trend in the comprehensive levels of both the EV industry and SEG.•The expansion of charging infrastructure plays a significant role in driving the growth of the EV industry.•Foreign investments are pivotal contributors to SEG.•There exists a robust interaction between the EV industry and SEG, progressing from a severe imbalance to marginal coordination and ultimately achieving high-quality coordination.•The growth of the EV industry fosters technological innovation and drives green advancements throughout the industry chain, ultimately enhancing SEG. This study examines the electric vehicle (EV) industry's impact on sustainable economic growth (SEG). Using the entropy weight method, it evaluates the EV industry's development and SEG levels. A coupling coordination degree model measures their interaction. Results show a positive trend in both areas, with charging infrastructure expansion and foreign investments being key drivers. The study finds a progressive shift from imbalance to high-quality coordination between the EV industry and SEG, highlighting their increasingly synergistic relationship. This growth in the EV industry fosters technological innovation and drives green advancements throughout the industry chain, thereby enhancing SEG.